Relasi Scrolling Culture Terhadap Kesehatan Mental Netizen Di Media Sosial - Latief, Rahmawati (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2025)
Scrolling culture is a lifestyle that has emerged as a result of the social media revolution that has changed communication and interaction strategies. This scrolling culture poses various benefits and threats to mental health for netizens. The factors that give rise to the presence of scrolling culture are caused by four things. First, individuals' dependence on smartphone technology that offers a variety of attractive platforms and accessible and informative features that greatly spoil netizens. Second, social media platforms offer core features that are a perfect integral part of the platform such as text, images, audio-visual features and even artificial intelligence (AI) features that color social media platforms. Third, data capitalism through algorithms that allow individuals to receive information about their social networks directly on their timeline with the aim of personalizing the netizen experience. Fourth, the dominance of the affective function of media in which these social media platforms are not only for obtaining information and contacting others, but also the frequent possibility of accessing relevant content, and consequently living interesting experiences, combined with the infinite scrolling and incessant influx of messages and notifications that are very convincing in ensuring continuous connectivity, despite the abundance of messages and unlimited connections will lead to fatigue, lethargy and information obesity. Keywords: Culture, Scrolling, Social Media